Grundtvig i politik op til 1830 - Wåhlin, Vagn (Grundtvig-studier, 1994)
Grundtvig in Politic until 1830-1831 By Vagn Wåhlin Vagn Wåhlin discusses the Grundtvig text, .Political Considerations., re-printed above, which was written in the year of the 1930 revolution. In the Danish United Monarchy the European revolutions gave rise to a demand for a wider citizen participation in politics through parliamentary institutions and a demand for a solution to the national problem of the position of Schleswig between the Kingdom and Holstein. In addition, the debate led to a discussion of and a demand for an extension of the civil rights, including in particular a specification of the character and extent of the freedom of the press. The present article discusses Grundtvig’s treatment of these and other political subjects in the pamphlet mentioned.In the article, the concept of politics is defined as the attempt by an individual or a group to influence the authoritative distribution of the material and spiritual wealth of the society, a definition that comes close to Grundtvig’s own view. The article does not intend an exhaustive account of Grundtvig’s political views, but aims to show how Grundtvig’s attitude in a number of earlier writings has emerged through his occupation with current events and considerable social philosophers. The decisive thing for Grundtvig, before and especially around and after the time of the pamphlet discussed here, was to present and promote a form of government, on a historical and pragmatic basis, for the benefit and welfare of the whole people, where freedom and power balanced each other, where the rulers were responsive to the voice of an enlightened citizenry, and where confidence, love and responsibility rather than selfishness prevailed among the members of the society and determined the purposeful actions of the whole people - all under Divine Providence. It is pointed out how Grundtvig takes account of the character of the Danish society as an agrarian society by emphasizing the peasantry as ideally the fundamental and stabilizing element in the state. Consequently Grundtvig stresses the primary production as the foundation of society, structured through the mutual love in freedom and the folk culture of the people - traits common to the nation - as the basis of the interaction of the citizens and hence the balance between their equality and freedom. Grundtvig doubts the general possibility or desirability of equality, and is of the opinion that inequality is a natural condition of life, but that this condition is counterbalanced by the mutual fellow feeling of the citizens. Grundtvig uses the social pact idea in his definition of the distribution of power between the consultative function of the people, expressing the general will of the public, and the executive power of the King. The consultative power of the citizens finds its expression through the public media, dependent on freedom of the press, and Grundtvig brings up the concrete proposal that the Schleswig question should be solved by letting the Schleswigers give expression to the general public will in the public press. Grundtvig defends the right of the citizens to revolt the moment their rights, for example their right of property, are violated, but he dissociates himself from revolutions which, in his opinion, lead to tyranny, the opposite of freedom. The article explains how trust in God’s Providence together with love is the condition of the King’s and the people’s trust in the viability of the above-mentioned relationship. Grundtvig’s political views have their foundation in his emphasis on the importance of Christianity for the universal-historical development and for a people’s fulfillment of its own destiny in it.